2018
DOI: 10.1007/s12325-018-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Better Understanding and Recognition of the Disconnects, Experiences, and Needs of Patients with Irritable Bowel Syndrome with Constipation (BURDEN IBS-C) Study: Results of an Online Questionnaire

Abstract: Introduction: The BURDEN IBS-C study was conducted to better understand the experiences, attitudes, and unmet needs of sufferers of irritable bowel syndrome with constipation (IBS-C) in comparison to the perceptions and challenges of healthcare providers (HCPs) who treat IBS-C patients. Methods: This was an author-developed, online questionnaire using KnowledgePanel Ò to survey individuals with IBS-C (N = 1311). HCPs participated in a complementary online questionnaire and were recruited separately (N = 331).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 16 publications
(26 reference statements)
4
49
0
Order By: Relevance
“…24,25,29,30 Physicians often prefer using objective and physical factors when defining constipation, whereas patient dissatisfaction may not necessarily be related to these factors. 31 In this regard, these diagnostic tools, designed based on patients' subjective symptoms, may overcome the inherent differences in perception of constipation between physicians and patients and thus are recommended to assess constipation for both clinical practice and research purposes. 28 In fact, a recent cross-sectional study reported that more than half of patients with CKD (n ¼ 180) who had less frequent bowel movements (defined as bowel frequency of once every 4 to 6 days per week or less) with abnormal stool form and gastrointestinal symptom(s) perceived their bowel health as "normal" or "more normal than abnormal."…”
Section: Prevalence Of Constipation In Ckd Diagnostic Criteriamentioning
confidence: 99%
“…24,25,29,30 Physicians often prefer using objective and physical factors when defining constipation, whereas patient dissatisfaction may not necessarily be related to these factors. 31 In this regard, these diagnostic tools, designed based on patients' subjective symptoms, may overcome the inherent differences in perception of constipation between physicians and patients and thus are recommended to assess constipation for both clinical practice and research purposes. 28 In fact, a recent cross-sectional study reported that more than half of patients with CKD (n ¼ 180) who had less frequent bowel movements (defined as bowel frequency of once every 4 to 6 days per week or less) with abnormal stool form and gastrointestinal symptom(s) perceived their bowel health as "normal" or "more normal than abnormal."…”
Section: Prevalence Of Constipation In Ckd Diagnostic Criteriamentioning
confidence: 99%
“…The substantial patient retention achieved in CONTOR not only highlights the success of combining mixed-mode surveys with pre-paid incentives and post-paid payments to engage participants in a longitudinal observational study, but may also illustrate patients' desire to share their experiences of living with IBS-C and CIC. Patients may find these conditions difficult to discuss; in previous survey-based analyses, feelings of embarrassment and self-consciousness related to IBS-C/CIC were commonly reported, particularly by those with more severe disease 9,10 . CONTOR participants' sustained commitment to the study suggests they found it important and/or fulfilling to communicate the impact of their symptoms and treatments on their lives.…”
Section: Discussionmentioning
confidence: 99%
“…CONTOR participants' sustained commitment to the study suggests they found it important and/or fulfilling to communicate the impact of their symptoms and treatments on their lives. Opportunities such as CONTOR that allow patients to safely share their disease journey may empower them to engage in this type of dialogue with their healthcare providers and help improve the patient experience with treatment for IBS-C/CIC 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations